Temperature-controlled microwave-vacuum drying of lactic acid bacteria: Impact of drying conditions on process and product characteristics. (May 2018) - Ambros, S.; Foerst, P.; Kulozik, U.
Abstract: An efficient drying process for high-value products such as bacterial cultures is characterized by high retention of viability or activity, but low energy demand. Microwave-vacuum drying was tested in this work as a new technique for the preservation of probiotics and starter cultures, which has the potential to fulfill all of these requirements. The impact of chamber pressure (7, 15, 30 mbar), microwave power (1–5 W g −1 ) and maximum product temperature (30–50 °C) on drying time, drying rate, efficiency of microwave input and survival rate of the model strain Lactobacillus paracasei ssp. paracasei F19 ( L. paracasei F19) was studied. Microwave drying time ranged from 50 to 240 min with microwave power as main influencing factor on drying behavior and efficiency. The maximum product temperature and vacuum pressure did not affect the drying time, absorbed energy and thus microwave efficiency significantly, but both parameters had a great impact on survival rate. The combination of 3 W g −1 microwave power input and 35 °C maximum temperature at a low chamber pressure of 7 mbar resulted in a very short drying time of 64 min, a high level of energy efficiency (27%) and also the best product quality in terms of survival rate (33%). Thus, a microwave-vacuum drying process is a potential alternative to conventional freeze or vacuum drying. Highlights: Microwave-vacuum drying as potential alternative to conventional freeze or vacuum drying. Drying behavior and efficiency are mainly influenced by microwave power. Maximum product temperature and vacuum level affect survival more than power input. Intermediate microwave power levels led to shortest drying time, most efficient process and highest survival rate.